Experimental and clinical possibilities of MR spectroscopy of the heart - Neubauer, S; Ertl, G; Krahe, T; Schindler, R; Hillenbrand, H; Lackner, K; Kochsiek, K (1991)
MR-spectroscopy of the heart is a relatively new technique for the study of various aspects of cardiac metabolism. The majority of results has so far been obtained with the isolated perfused heart. Here, 31P-MR spectroscopy can be employed to measure high-energy phosphate metabolism and intracellular pH repeatedly and non-invasively. Using a technique called saturation transfer, velocities of enzymatic reactions, such as the creatine kinase reaction, can be measured. Intra- and extracellular Na+ and K+ concentrations can be registered with 23Na- and 39K-MR in conjunction with shift reagent. 13C-MR can be used to tackle carbohydrate metabolism. In-situ-R-spectroscopy allows determination of high-energy phosphates in intact large mammals. Clinical applications of MR-spectroscopy remain to be defined; preliminary results indicate high diagnostic and prognostic potential for patients with coronary artery disease and congestive heart failure.